In silico Approaches of Azadirachta indica polypeptides exhibiting antimicrobial and anticancer potential - Mohammed Al Saiqali; Krishnamurthy Nakuluri A. Venkateshwar Reddy
Medicinal plants are a vital source of natural bioactive peptides with broad therapeutic and pharmaceutical applications. These peptides are emerging as a viable alternative to traditional anticancer drugs and conventional antibiotics and potentially have the ability to reduce adverse side effects. This study concentrated on the anticancer and antibacterial efficacy of three bioactive low molecular weight polypeptides (11, 13, and 14 kDa) extracted from neem leaves. The analysis employed SDS-PAGE peptide profiling followed by sequence elucidation via MALDI TOF spectrometry. The three-dimensional (3D) structural models and the target proteins BCL-2 and Sortase A were constructed using Modeller9v7 software. The structural integrity of these models was assessed through molecular dynamics simulations and validated with the SAVES program. Molecular interactions between the peptides and cancer-associated protein BCL-2, alongside the bacterial enzyme Sortase A, were explored using molecular docking techniques facilitated by GOLD 3.0.1 software. The docking analysis revealed that the polypeptides, designated as polypeptide 1 (11kDa), polypeptide 2 (13kDa), polypeptide 3 (14 kDa), exhibited substantial binding affinity towards both BCL-2 and Staphylococcus aureus Sortase A, with binding energies of 26.96, 21.59, and 26.11 Kcal/mol, respectively. They also inhibited BCL-2 with binding energies of 27.00, 23.13, and 20.31 Kcal/mol, respectively. Remarkably, polypeptide 1(11 kDa) showed superior efficacy in both anticancer and antimicrobial activities, underscoring its potential as a candidate for developing novel therapeutic agents against anticancer and antimicrobial infections. The findings of this study highlight the promising role of plant-derived bioactive polypeptides in the treatment of cancer and microbial infections